Kedudukan Mahkamah Konstitusi dalam Mekanisme Impeachment: Studi Komparasi Negara Republik Indonesia dan Republik Federal Jerman - Anfal Kurniawan; Martitah (UIN Sunan Kalijaga Yogyakarta, 2023)
This research examines the comparison of impeachment schemes and the position of the Constitutional Court of the Republic of Indonesia and the Federal Republic of Germany using comparative legal studies and the theory of legal objectives. The impeachment of the Head of State in this case the President in the constitutional system has tensions in normative and political aspects. Therefore, this research will describe how the position of the Constitutional Court as the Guardian of Constitution and Democracy in facing the issue of impeachment. With comparative legal studies, the researcher tries to compare the impeachment scheme between the Republic of Indonesia and the Federal State of Germany with a Normative Juridical Approach and uses qualitative data, through an analysis scheme that is infersial description by sourcing documents, books, and laws. The results show that the impeachment scheme between the Republic of Indonesia and the Federal State of Germany has similarities in that the Constitutional Court has the authority to adjudicate in processing impeachment mechanisms, although there are fundamental technical differences where the Court in Germany does not have a direct role in the dismissal of the Head of State but focuses on constitutional testing of laws, while in Indonesia the Court is integrally involved in substantive verification of charges against the president and vice president. In addition, the Constitutional Court has the responsibility to safeguard the proportionality of charges against the president and vice president from normative and political tensions. This aims to maintain the objectivity of case resolution, without political intervention and the vagueness of the norms in question as the concept of legal objectives in maintaining certainty, justice and expediency. Abstrak: Penelitian ini mengkaji perbandingan skema pemakzulan atau impeachment serta kedudukan Mahkamah Kosntitusi Republik Indonesia dan Republik Federal Jerman menggunakan studi hukum komparatif dan teori tujuan hukum. Pemakzulan Kepala Negara dalam hal ini Presiden dalam sistem ketatanegaraan memiliki ketegangan secara aspek normatif dan politis. Oleh karena itu, penelitian ini akan menguraikan bagaimana kedudukan Mahkamah Konstitusi sebagai The Guardian of Constitution and Democracy dalam menghadapi persoalan impeachment. Dengan comparative legal studies peneliti mencoba membandingkan skema impeachment antara Negara Republik Indonesia dengan Negara Federal Jerman dengan Pendekatan Yuridis Normatif serta menggunakan data kualitatif, melalui skema analisis yang bersifat diskripsi infersial dengan bersumberkan dokumen-dokumen, buku, dan Undang-Undang. Hasil penelitian menunjukan bahwa skema impeachment antara Negara Republik Indonesia dan Negara Federal Jerman memiliki persamaan bahwa Mahkamah Konstitusi memiliki kewenangan di dalam proses mengadili dalam memproses mekanisme pemakzulan, meskipun terdapat perbedaan teknis mendasar dimana Mahkamah di Jerman tidak memiliki peran langsung dalam pemberhentia Kepala Negara melainkan berfokus pada pengujian konstitutional Undang-Undang, sedangkan di Indonesia Mahkamah terlibat secara integral terkait verifikasi substantif dakwaan terhadap presiden dan wakil presiden. Selain itu, Mahkamah Konstitusi memiliki tanggung jawab untuk menjalakan proporsionalitas dakwaan terhadap presiden dan wakil presiden dari adanya ketegangan secara normative dengan ketegangan politis. Hal tersebut bertujuan untuk menjaga obyektifitas penyelesaian perkara, tanpa adanya intervensi politis dan kekaburan norma yang dipermasalahkan sebagaimana konsep tujuan hukum dalam menjaga kepastian, keadilan, dan kemanfaatan